2021
DOI: 10.21632/saki.4.1.1-16
|View full text |Cite
|
Sign up to set email alerts
|

Pendekatan Vousinas Fraud Hexagon Model dalam Mendeteksi Kecurangan Pelaporan Keuangan

Abstract: Penelitian ini bertujuan untuk menganalisis pengaruh model fraud hexagon; stimulus (tekanan), kesempatan, rasionalisasi, kemampuan, ego dan kolusi terhadap kecurangan pelaporan keuangan dengan menggunakan pengukuran model F-Score pada perusahaan sektor manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2017-2019. Sampel yang digunakan dalam penelitian berjumlah 97 perusahaan manufaktur di Indonesia dengan jumlah observasi sebanyak 291. Penelitian menggunakan teknik analisis regresi logistik.Hasil pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
2
16

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 14 publications
(38 reference statements)
3
6
2
16
Order By: Relevance
“…Hypothesis testing of the variable change of directors shows a regression coefficient value of 0.997 and a significance level of 0.001 so that the sixth hypothesis is accepted because it is below the significance level of 0.05. This research is the same as research by Sari et al (2022) and Jannah et al (2021) which revealed that changes in directors have an effect on financial statement fraud.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Hypothesis testing of the variable change of directors shows a regression coefficient value of 0.997 and a significance level of 0.001 so that the sixth hypothesis is accepted because it is below the significance level of 0.05. This research is the same as research by Sari et al (2022) and Jannah et al (2021) which revealed that changes in directors have an effect on financial statement fraud.…”
Section: Discussionsupporting
confidence: 60%
“…Research conducted by shows that the nature of the industry and changes in the board of directors have a positive effect on financial statement fraud, while external pressure, auditor changes, CEO duality and political connections have a negative effect on financial statement fraud. Research conducted by Jannah et al (2021) shows that external pressure, auditor changes, changes in directors, and collusion have a positive effect on financial statement fraud, while financial stability, financial targets, supervisory ineffectiveness, and CEO duality have a negative effect on financial statement fraud. Meanwhile, research from Novarina & Triyanto (2022) shows that auditor opinion and the number of CEO photos have a positive effect on financial statement fraud, while external pressure, changes in the board of directors, the nature of the industry and collusion have a negative effect on financial statement fraud.…”
Section: Introductionmentioning
confidence: 99%
“…Fraud dilakukan karena pelaku kecurangan percaya bahwa manajemen lebih bekerja keras dibandingkan dengan pemilik perusahaan. Maka pihak manajemen berhak mendapatkan profit yang tinggi sehingga manajemen membenarkan atas kecurangan yang dilakukan, hal inilah yang menjadi penghubung antara teori agency dengan rasionalisasi (Jannah & Rasuli, 2021). Prinsip akrual mendeskripsikan rasionalisasi dalam pelaporan laporan keuangan karena berhubungan dengan pengambilan keputusan manajemen dalam perusahaan sehingga total accrual berpengaruh dalam kecurangan laporan keuangan (Faradiza, 2019).…”
Section: Pengaruh Total Accrual Ratio Sebagai Proksi Rationalization ...unclassified
“…Arogansi merupakan sifat sombong dan sikap prioritas yang muncul akibat keyakinan bahwa seseorang tidak berada dalam pengendalian internal. Sifat arogan akan menjadi penyebab terjadinya fraud karena dengan sifat arogannya seorang CEO akan melakukan apa saja untuk mencegah posisinya berubah (Jannah & Rasuli, 2021). CEO duality merupakan dominasi kekuasaan CEO yang memiliki jabatan lain dalam perusahaan.…”
Section: Pengaruh Ceo Duality Sebagai Proksi Arrogance Dalam Mendetek...unclassified
See 1 more Smart Citation